Enhanced immunogenicity and protective efficacy of a tetravalent dengue DNA vaccine using electroporation and intradermal delivery. Issue 32 (26th July 2019) - Williams, Maya; Ewing, Dan; Blevins, Maria; Sun, Peifang; Sundaram, Appavu K.; Raviprakash, Kanakatte S.; Porter, Kevin R.; Sanders, John W.
Abstract: Phase 1 clinical trials with a DNA vaccine for dengue demonstrated that the vaccine is safe and well tolerated, however it produced less than optimal humoral immune responses. To determine if the immunogenicity of the tetravalent dengue DNA vaccine could be enhanced, we explored alternate, yet to be tested, methods of vaccine administration in non-human primates. Animals were vaccinated on days 0, 28 and 91 with either a low (1 mg) or high (5 mg) dose of vaccine by the intradermal or intramuscular route, using either needle-free injection or electroporation devices. Neutralizing antibody, IFN-γ T cell and memory B cell responses were compared to a high dose group vaccinated with a needle-free intramuscular injection delivery device similar to what had been used in previous preclinical and clinical studies. All previously untested vaccination methodologies elicited improved immune responses compared to the high dose needle-free intramuscular injection delivery group. The highest neutralizing antibody responses were observed in the group that was vaccinated with the high dose formulation via intradermal electroporation. The highest IFN-γ T cell responses were also observed in the high dose intradermal electroporation group and the CD8 + T cells were the dominant contributors for the IFNγ response. Memory B cells were detected for all four serotypes. More than a year after vaccination, groups were challenged with dengue-1 virus. Both the low and high dose intradermal electroporation groups had significantly fewer days of dengue-1 virus RNAemia compared to the control group. The results from this study demonstrate that using either an electroporation device and/or the intradermal route of delivery increases the immune response generated by this vaccine in non-human primates and should be explored in humans.